Schiff bases containing a furoxan moiety as potential nitric oxide donors in plant tissues - Georgescu, Emilian (PLoS One, 2018)
Stable Schiff bases containing a furoxan moiety are synthesized as single regioisomers by the reaction of 3-methyl-2-oxy-furazan-4-carbaldehydewith various amino compounds at room temperature. The structures of synthesized compounds were fully characterized by multinuclear NMR spectroscopy and X-ray crystallography. The effect of synthesized Schiff bases containing a furoxan moiety on biological generation of reactive oxygen species and nitric oxide in plant tissues was investigated for the first time by fluorescence microscopy and the released NO identified as nitrite with Griess reagent. There is a good correlation between the biological generation of NO determined by fluorescence microscopy and with Griess reagent. Some of the synthesized compounds exhibited both nitric oxide and reactive oxygen species generation abilities and represent potential NO donors in plant tissues.